Current status on metabolic engineering for the production of l-aspartate family amino acids and derivatives. (December 2017) - Li, Yanjun; Wei, Hongbo; Wang, Ting; Xu, Qingyang; Zhang, Chenglin; Fan, Xiaoguang; Ma, Qian; Chen, Ning; Xie, Xixian
Highlights: l -Aspartate family amino acids (AFAAs) are important in human and animal diet. Five-word strain breeding strategy "enter, flow, moderate, block, exit" are proposed. Genetic modifications in central metabolic pathways for AFAAs production. Metabolic pathways of AFAAs and derivatives and regulations involved. Metabolic engineering in AFAAs metabolic pathways based on different strategies. Abstract: The l -aspartate amino acids (AFAAs) are constituted of l -aspartate, l -lysine, l -methionine, l -threonine and l -isoleucine. Except for l -aspartate, AFAAs are essential amino acids that cannot be synthesized by humans and most farm animals, and thus possess wide applications in food, animal feed, pharmaceutical and cosmetics industries. To date, a number of amino acids, including AFAAs have been industrially produced by microbial fermentation. However, the overall metabolic and regulatory mechanisms of the synthesis of AFAAs and the recent progress on strain construction have rarely been reviewed. Aiming to promote the establishment of strains of Corynebacterium glutamicum and Escherichia coli, the two industrial amino acids producing bacteria, that are capable of producing high titers of AFAAs and derivatives, this paper systematically summarizes the current progress on metabolic engineering manipulations in both central metabolic pathways and AFAA synthesis pathways based on the category of the five-word strain breeding strategies: enter, flow, moderate, block and exit.